Contribution of Pesantren Miftahul Ula Nganjuk in Community-Based Education Development - Muh Barid Nizarudin Wajdi; Yuni Masrifatin; Syamsul Arifin; Abdul Haris; M. Samsul Hady (EDUTEC : Journal of Education And Technology, 2022)
Pondok Pesantren or Islamic Boarding School has become a sub-culture of the Indonesian people, assimilated with the community. Islamic boarding school students and alumni have long participated in community activities. This article aims to explore the role of Miftahul Ula Islamic Boarding School in community development through education. This research was conducted using the ABCD approach. The results showed that the Miftahul Ula Islamic Boarding School could develop the community through education by building formal and non-formal institutions that were recognized by the government, so that the surrounding community could fulfill their needs, especially in the field of education.